Trichoptera of Serra da Jibóia, Bahia, Brazil: new species of Helicopsyche (Helicopsychidae) and new records - Vilarino, Albane; Calor, Adolfo R. (Zootaxa, 2017)
Located in Northeast Region of Brazil, Bahia state, Serra da Jibóia is a mountain range situated between the Atlantic Forest and semiarid Caatinga ecoregions. In the present work the diversity of the caddisfly fauna from Serra da Jibóia was investigated during a seven-year period. We collected 3,472 adults, identifying 40 caddisfly species belonging to 26 genera and 11 families, of which 8 species are new records for the state. In this inventory we present the composition, abundance, and sex ratios of the species identified in the study. We also described a new species, Helicopsyche (Feropsyche) guariru n. sp., recognized by having the inferior appendage elongate, tapering to a pointed apex, and its basomesal lobe reduced to a small process bearing one or two short spine-like setae apically.